Results with Posterior Scleral Reinforcement for Progressive Highly Myopic Children in Hungary - Széll, Noémi; Boross, Adrienn; Facskó, Andrea; Sohajda, Zoltán (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose We have been performing posterior scleral reinforcement in our ophthalmological department since 1992 on progressive highly myopic eyes. Here, we report on our results with this technique in the foregoing 7 years in a retrospective comparative design.Methods Thirty-eight eyes of 32 patients, operated according to Snyder-Thompsonʼs method, were enrolled in this study, and a control group of 9 age- and myopia-matched childrenʼs 14 eyes was built for comparison. Pre- and postoperative best-corrected visual acuity, subjective refractive error (spherical equivalent of spectacle dioptres), and axial length were recorded. Changes within groups were calculated, as well as baseline parameters and their changes during follow-up, and compared between the groups. Correlation analysis was performed to identify factors that could influence myopia progression.Results Myopic progression was significantly lower in the operated than in the nonoperated group, both in terms of mean annual axial length as well as refractive error changes (0.21 ± 0.08 mm versus 0.49 ± 0.19 mm and 0.18 ± 0.29 D versus 0.6 ± 0.33 D, respectively). Mean overall visual improvement was more explicit in operated eyes as compared to those left untreated (0.15 ± 0.09 versus 0.01 ± 0.1). No association of any factor with myopia progression could be identified. We encountered no serious or lasting complications.Conclusion In our clinical practice, posterior scleral reinforcement according to Snyder-Thompson proved to be a safely applicable and effective surgical method to stop or significantly retard pathological increases in axial length and dioptres, and thus can help prevent the onset of myopic degenerative lesions, and irreversible visual impairment in the long run.
Keywords: progressive high myopia; posterior scleral reinforcement; myopia control